Association Between Diet Quality & Rate of Gestational Weight Gain Among Pregnant Women in Dhulikhel, Nepal. (29th May 2020) - Tiderencel, Kelly; Sackey, Joachim; Rigassio-Radler, Diane; Barrett, Emily; Shrestha, Archana; Rawal, Shristi
Abstract: Objectives: The National Academy of Medicine (NAM) guidelines recommend linear gestational weight gain (GWG) in the 2 nd and 3 rd trimester with appropriate rate defined based on pre-pregnancy BMI. Here we prospectively examined the association between diet quality and GWG rate from 2 nd to 3 rd trimester among women receiving prenatal care in a periurban hospital in Nepal. Methods: A pilot cohort of singleton pregnant women (N = 101; age 25.9 ± 4.1 years) was recruited from a tertiary, periurban hospital in Nepal. In the 1st trimester, diet quality was assessed from the adapted Nepali version of the PrimeScreen questionnaire, which assigned diet quality scores (range 0–42; higher scores for better quality) based on consumption frequency of 12 healthy and 9 unhealthy food groups. The GWG rate was calculated as the measured weight at the early-to-mid 3 rd trimester (28–35 wks) minus the weight at 2 nd trimester (13–25 wks), divided by the number of weeks in between. Linear regression estimated the association between diet quality and GWG rate, adjusting for a priori covariates including age, education, ethnicity, pre-pregnancy BMI, and nausea/vomiting. The adequacy of GWG rate was also categorized as inadequate, adequate, or excessive using NAM guidelines. Results: Most women were of normal (55.4%) or overweight (33.7%) BMI status pre-pregnancy. The mean GWG rate in mid-to-late pregnancy was 0.46 ± 0.2 kg/wk and the mean diet quality score was 23.6 ± 2.5. Based on pre-pregnancy BMI, 49.4% of women had excessive GWG rate, while nearly equal numbers had either adequate GWG or inadequate GWG rate. Pre-pregnancy BMI and GWG rate were inversely correlated ( r = −0.21, P = 0.049). Education level was positively associated with both GWG rate ( P = 0.01) and adequacy of GWG ( P = 0.02). There was no significant association between diet quality and the GWG rate [adjusted β (95% CI) = −0.02 (−0.05, 0.01); P = 0.14]. The mean GWG rate was marginally lower (0.44 vs. 0.57 kg/wk; P = 0.06) among those with high versus low (2 + servings vs. 0–1 serving/wk) intake of red meat; similar findings were seen when comparing red meat intake between women with excessive versus adequate GWG (Cramer's V = 0.2; P = 0.06). Conclusions: While overall diet quality is not related to GWG among Nepali women, a high intake of red meat may be a potential risk factor for excessive GWG in this population. Funding Sources: Rutgers Global Health Institute.